Kynurenines in CNS disease: regulation by inflammatory cytokines - Campbell, Brian M.; Charych, Erik; Lee, Anna W.; Möller, Thomas (Frontiers in Neuroscience, 2014)
The kynurenine pathway metabolizes the essential amino acid tryptophan and generates a number of neuroactive metabolites collectively called the kynurenines. Segregated into at least two distinct branches, often termed the “neurotoxic” and “neuroprotective” arms of the kynurenine pathway, they are regulated by the two enzymes kynurenine 3-monooxygenase and kynurenine aminotransferase, respectively. Interestingly, several enzymes in the pathway are under tight control of inflammatory mediators. Recent years have seen a tremendous increase in our understanding of neuroinflammation in CNS disease. This review will focus on the regulation of the kynurenine pathway by inflammatory mediators as it pertains to neurodegenerative and psychiatric disorders.